The Relationship Between Social Anxiety and Nomophobic Tendencies in Migrant Students in Makassar City - Magfirah, Nurul; Ridfah, Ahmad; Ismail, Ismalandari (Polteknik Ilmu Pemasyarakatan, 2023)
Overseas students who experience social anxiety will feel anxious when communicating and face to face, so they use smartphones more which can trigger the emergence of nomophobia tendencies. This study aims to determine the relationship between social anxiety and nomophobia tendencies among overseas students in Makassar City. The subjects in this study were overseas students studying in Makassar City aged 18 to 25 years. The sampling technique used is accidental sampling. Nomophobia tendency is measured using a scaleNomophobia Questionnaire (NMP-Q), social anxiety was measured using the Social Anxiety Scale for Adolescents (SAS-A). Hypothesis testing using Rank Spearman correlation analysis. The results of the analysis obtained were p = 0.003 <0.005 or there was a relationship between social anxiety and the tendency of nomophobia among overseas students in the city of Makassar. The correlation coefficient of social anxiety variable with nomophobia tendency is 0.228 or it is classified as weak. The conclusion in this study shows that there is a relationship between social anxiety and nomophobia tendencies in overseas students in Makassar City. The social anxiety possessed by the subjects in this study was moderate, while the tendency of nomophobia possessed by the subjects in this study was high.